Chromocene, ferrocene, cobaltocene, and nickelocene derivatives with isopropyl and methyl or trimethylsilyl substituents - Bauer, Heiko; Weismann, Julia; Saurenz, Dirk; Färber, Christian; Schär, Marion; Gidt, Wjatscheslaw; Schädlich, Ina; Wolmershäuser, Gotthelf; Sun, Yu; Harder, Sjoerd; Sitzmann, Helmut (Journal of Organometallic Chemistry, 2016)
From sodium 2,3-diisopropyl-1,4-dimethyl-cyclopentadienide and MBr2(dme) (M = Fe, Co, Ni) the corresponding ferrocene (1), cobaltocene (2) and nickelocene (3) could be obtained as pure, crystalline solids. From an analogous reaction of sodium 2,3,5-triisopropyl-1,4-dimethyl-cyclopentadienide with FeCl2, only the mixed-substituted ferrocene (Cp-3(2))(Cp-2(2))Fe (4) could be crystallized (Cp-3(2) = 2,3,5-triisopropyl-1,4-dimethyl-cyclopentadienyl, Cp-2(2) = 2,3-diisopropyl-1,4-dimethyl-cyclopentadienyl). The trimethylsilyl substituted ferrocene (5) and nickelocene (6) were synthesized from the corresponding metal halides and potassium 2,3-diisopropyl-1,4-dimethyl-5-trimethylsilyl-cyclopentadienide as well as a series of chromocenes with silylated or alkylated cyclopentadienyl ligands (7-10) from chromium(II) acetate. Octaisopropylnickelocene (11) has been obtained and converted to octaisopropylnickelocenium hexafluorophosphate (12). 1,2,3,4-tetraisopropylnickelocenium tetrabromoaluminate (13) was obtained from tetraisopropylcyclopentadienylnickel(II) tetrabromoaluminate and nickelocene. Crystal structures have been obtained for metallocenes 1-5, 7-9, and 11. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkylcyclopentadienyl ligand; Ferrocene; Cobaltocene; Nickelocene; Chromocene; Crystal structure